QUALITATIVE AND QUANTITATIVE ANALYSIS OF WATER CONING AND BREAKTHROUGH TIME PREDICTION ON ZNC FIELD - Aqlyna Fattahanisa; Rini Setiati; Arinda Ristawati; Puri Wijayanti (Journal of Petroleum and Geothermal Technology, 2023)
Given the current public need for oil and gas as a primary energy, all oil and gas companies need to increase production to meet this demand. One of the things companies usually do to achieve this is to evaluate and analyze the productivity of each well. Of course, production decreases from time to time, so the company must try to increase its production. One of the reasons for the decline in oil production from the ZNC-1 well in the ZNC Field is the production of excessive water content. There are several factors that cause excessive water content in oil wells, and this is called water coning. The method used to determine the occurrence of the water cone problem requires qualitative and quantitative analysis. In using qualitative analysis, two analyzes were carried out, including an analysis of the production history of the well and an analysis of the Chan Diagnostic Plot showing bottom-water coning problems with late-time channeling. Meanwhile, based on the quantitative results, the critical flow rate of the ZNC-1 well calculated using the Bornazel and Jeanson method is 167 STB/D. With these results, the value of the critical flow discharge is greater than the actual discharge, which is 291.3 STB/D. Thus it can be ascertained that there has been water coning in the ZNC-1 well. After that, the breakthrough time obtained by the Bournazel and Jeanson method was 361.3 days.